40th AIAA Aerospace Sciences Meeting &Amp; Exhibit 2002
DOI: 10.2514/6.2002-773
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the detonation front in gases

Abstract: We have carried out simultaneous visualizations of a chemical species (OH) and density gradients in the reaction zones of propagating detonations. We have directly imaged the characteristic shape of the chemical reaction zone and correlated this with the instability of the front. The observations have sufficient resolution to clearly see the variation in the reaction zone structure associated with leading shock velocity oscillations and complex flow behind the triple points associated with the intersection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The ZND model [1] was developed by modifying the C-J theory to introduce the induction and heat release zones to mimic the chemical reactions. Although the ZND detonation structure is different from the experimental observations, it initiated the new research by considering both thermodynamic parameters and hydrodynamic scales together, which shows the promising direction of the future experimental and numerical investigations on detonation dynamic scales, wave front structures and cellular detonation cells [2,3] . Further study showed that the detonation front is of the three-dimensional structure that consists of incident shocks, Mach stems, transverse waves, reaction zones and shear layers.…”
Section: Introductionmentioning
confidence: 98%
“…The ZND model [1] was developed by modifying the C-J theory to introduce the induction and heat release zones to mimic the chemical reactions. Although the ZND detonation structure is different from the experimental observations, it initiated the new research by considering both thermodynamic parameters and hydrodynamic scales together, which shows the promising direction of the future experimental and numerical investigations on detonation dynamic scales, wave front structures and cellular detonation cells [2,3] . Further study showed that the detonation front is of the three-dimensional structure that consists of incident shocks, Mach stems, transverse waves, reaction zones and shear layers.…”
Section: Introductionmentioning
confidence: 98%